Consumer sales remedies in US and EU comparative perspective / Sanne Jansen. - Jansen, S. (Sanne) (Intersentia, 2018)
This book is an in-depth study of the US and EU approaches towards consumer sales remedies. It does not limit itself to a mere comparison of the hierarchy of consumer sales remedies but covers the topic comprehensively, also examining (extra)judicial application of remedies and notification duties. Whereas EU rules prescribe a very strict hierarchy of remedies that are often misunderstood by consumers, and are very favourable towards the remedy of specific performance (or performance in kind), in the US a strong preference for damages can be found. This means that consumers often do not know which remedy they are exactly entitled to or how to invoke it in a correct manner. Learning from both systems, Consumer Sales Remedies in US and EU Comparative Perspective provides a valuable and insightful contribution to the discussion of what the organisation of remedies should look like to best protect consumers. It is written at a time when the EU is considering a 'new' consumer sales Directive, and US scholars are working on the restatement of consumer contract law. It proposes to give consumers a free choice, limited by good faith and proportionality only. Dr Sanne Jansen is a judicial trainee in Antwerp, Belgium and research fellow at the Institute for the Law of Obligations at KU Leuven, Belgium. She is a member of the editorial board of the DCCR and TBH.